Psychometric Properties of Knowledge, Attitude, and Practice on Pharmacogenovigilance in Drug Safety Questionnaire in Medicine and Pharmacy Students: based on Exploratory Factor Analysis - Adamu Yau, Rohayah Husain, Aniza Abd Aziz, Mohd Khairi Bin Zahri Johari, Ab Fatah Bin Rahman, Ramadan Mohamed Elkalmi, Ya‟u Jamilu, Mainul Haque (Journal of Applied Pharmaceutical Science, 2015)
Integration of Pharmacogenomics and Pharmacovigilance in the curricula of future healthcare professionals is essential towards individualized medicine and drug safety. Researchers are lacking in Knowledge, attitude and practice regarding pharmacogenovigilance in drug safety among Malaysian future health professionals. This study is to develop and validate a reliable questionnaire for evaluation of knowledge, attitude and practice of future Doctors and Pharmacists concerning Pharmacogenovigilance in drug safety. A 49-item self-administered questionnaire was developed from the literature. The content was validated by a panel of relevant experts followed by face validity. A pilot study on 100 respondents was conducted for reliability, followed by a cross-sectional study involving 247 participants in factor analysis. The content validity index of the whole questionnaire was 0.8%. The overall Cronbach’s Alpha was 0.8, with P
Keywords: Pharmacogenovigilance, Questionnaire, Factor analysis, KAP.